Dinamika emosional dan perkembangan kepribadian anak sekolah dasar dalam karya sastra anak di pondok Kanak-Kanak darussalam - Muh Iqbal Syafii Iqbal Syafii (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This research was conducted due to problems related to the emotions and personality of elementary school-aged children in children's literature at the Darussalam Kindergarten. This problem is a complex process, which can be divided into four main domains, namely physical, intellectual (including cognition and language), and emotional and social (including moral development for elementary school children. This research aims to describe how elementary school-aged children develop emotionally and personality through children's literature. This research uses a qualitative approach method with a descriptive study type. The focus is on one group of subjects which has more A high emotional soul, namely in grade 5, to gain a deep understanding in a real context.The data collection procedure was through observation, interviews, and documentation. The data obtained was then analyzed interactively through data presentation and drawing conclusions to see the conditions in the location as a whole. The results of the study indicate that children's emotions and personalities are the author will examine the emotional and social development of elementary school-aged children. Emotional and social development is a child's sensitivity to understanding the feelings of others when interacting in everyday life. This socio-emotional development cannot be separated from one another. When discussing children's social development, it must intersect with children's emotional development. Keywords: Emotional Development, Social, Elementary School Children